Mutational landscape of primary and recurrent glioblastoma reveals potentially actionable SNVs including WNT pathway variation. (31st January 2018) - Ellis, Hayley; Sahm, Felix; Schrimpf, Daniel; Stupnikov, Alexei; Wadsley, Mark; Wragg, Christopher; McArt, Darragh; Kurian, Kathreena
Abstract: We used Next-Generation sequencing (NGS) panels to examine somatic variation in a cohort of 41 patients, 8 of which had matched primary biopsies and recurrent biopsies from subsequent tumour resection. 38/41 (92%) of the initial tumours harbour at least one variation in a gene which interacts with the RTK/Ras/PI(3)K pathway. 6/41 (15%) of initial tumours have an SNV in the IDH pathway. 27/41 (66%) of the initial biopsy samples have at least one SNV in the Wnt signalling pathway. 29/41 (71%) of initial tumours have at least one SNV in the p53 DNA damage repair pathway, and 12/41 (29%) have an SNV in the Rb cell-cycle regulation pathway. 3/41 (7%) of initial tumours have an SNV in the Nodal TGF-β signalling pathway for chromatin remodelling and pattern development, and 3/41 (7%) samples have a G-protein gene variation. Of the recurrent tissue samples, 6/8 (75%) have at least one somatic gene variation in the RTK/Ras/PI(3)K pathway, and 2/8 (25%) samples have an SNV in the IDH pathway. 3/8 (37.5%) have an SNV in the WNT signalling pathway, 4/8 (50%) have an SNV in the P53 pathway and no variation was identified in the Rb pathway. In 1/8 (12.5%) recurrent samples had an SNV in the Nodal TGF-β signalling pathway was identified, and 2/8 (25%) have a G-protein gene variation. Of the initial biopsy samples, 19/41 (46%) harboured at least one potentially actionable SNV. Of the recurrent tissue samples, 4/11 (36%) had at least one actionable SNV. Of the matched recurrent tumours, 6/8 (75%) contain SNVs that were present in the second tumour, as well as variation lost and gained. In 2/8 (25%) recurrent tumours, variation does not appear to correlate with the initial tumour. In conclusion, mutational analysis of primary and recurrent glioblastoma reveals potentially actionable SNVs including WNT pathway variation.